Anti-fouling high-voltage electrocatalytic activity polyvinylidene fluoride uranium adsorption material and preparation method thereof
Anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material prepared by physical blending technology and frozen phase conversion method solves the problem of dense structure and microbial adhesion during the process of uranium extraction in seawater. , achieving efficient uranium adsorption and antibacterial properties.
Patent Information
- Application Number
- CN202411620547.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polyvinylidene fluoride materials have dense structures during the extraction of uranium in seawater that are not conducive to catalytic reactions, and are difficult to inhibit the adhesion of marine microorganisms, affecting the adsorption performance and service life of uranium.
Using physical blending technology, polyvinylidene fluoride is blended with amidoxime-polyacrylonitrile and Bi4Ti3O12/SnO2 piezoelectric heterojunction through dimethyl sulfoxide as solvent, and anti-fouling is made by frozen phase conversion method. high voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material.
It improves the adsorption selectivity and removal rate of the material to uranyl ions, has excellent antibacterial properties, and extends the service life of the material.
Smart Images

Figure CN119455910A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of uranium adsorption materials, and in particular to an anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material and a preparation method thereof. Background Art
[0002] With the development of global industrialization, the over-exploitation and use of fossil fuels has triggered the greenhouse effect and caused many environmental problems. Nuclear power has the advantages of low operating costs, low carbon emissions, safety and reliability, and is an important way to achieve the goals of "carbon peak regulation and carbon neutrality". As an important nuclear fuel, uranium reserves determine the development of nuclear energy. Compared with the limited uranium reserves on land, the ocean is an inexhaustible treasure trove of uranium. However, the concentration of uranyl ions in seawater is extremely low, estimated to be about 3.3 micrograms per liter. There are a large number of competing ions and microorganisms in seawater, which compete with uranyl ions for active sites. Therefore, extracting uranium from seawater is full of challenges. Therefore, it is crucial to develop a new strategy to extract uranium from seawater.
[0003] Polyvinylidene fluoride (PVDF) is an ideal carrier material with good mechanical properties, chemical resistance and high piezoelectric coefficient, which makes it an ideal material for loading piezoelectric catalysts and performing piezoelectric catalysis. However, PVDF has five crystalline phases, namely α, β, γ, δ and ε, among which the β phase has the highest piezoelectric activity. Studies have shown that it is easier to obtain β-phase PVDF by crystallization below 70°C. Therefore, manufacturing porous membranes with high piezoelectric activity is an effective strategy to improve the catalytic performance of materials, because abundant pores can provide more reactive active sites and enhance the piezoelectric response of materials. In addition, the high piezoelectric response can prevent microbial contamination, thereby improving the durability of the catalyst.
[0004] However, the dense structure of the polyvinylidene fluoride membrane itself is not conducive to catalytic reaction and its own functional groups cannot adsorb uranyl ions, which affects the adsorption capacity and selectivity of polyvinylidene fluoride materials for uranyl ions. In seawater environment, the surface of polyvinylidene fluoride materials is easily attached by marine microorganisms, which seriously affects its uranium adsorption performance and service life. Therefore, polyvinylidene fluoride materials mainly face the following problems in the process of extracting uranium from seawater:
[0005] 1. The structure of polyvinylidene fluoride materials is dense, which is not conducive to catalytic reaction. The structure of traditional polyvinylidene fluoride film materials is dense, and it is difficult for uranyl ions to bind to the active sites, resulting in a slow reaction rate.
[0006] 2. Existing polyvinylidene fluoride materials are difficult to inhibit the attachment of marine microorganisms. PVDF is a white powdery semi-crystalline polymer, known for its good flexibility, chemical corrosion resistance, excellent piezoelectricity, dielectricity, thermoelectricity and high dipole moment, and is a good carrier for piezoelectric materials. However, there are no active groups on the surface of PVDF, which cannot resist potential bacterial contamination. Bacteria attach to the surface of polyvinylidene fluoride, reducing the activity of the adsorption sites, and ultimately causing the failure of polyvinylidene fluoride-based materials.
[0007] After searching, Chinese patent document CN112371175A discloses a CN / Li NbO3 heterojunction, and based on the CN / Li NbO3 heterojunction, a CN / Li NbO3 / PVDF piezoelectric photocatalytic composite membrane with a three-dimensional macroporous morphology is prepared by a frozen phase conversion method. Its porosity is high, providing more reaction contact area, which is beneficial to the interfacial contact between the photocatalytic composite membrane and water molecules, and exposing more CN / Li NbO3 heterojunction active sites. The CN / Li NbO3 / PVDF piezoelectric photocatalytic composite membrane provided by the invention can solve the problem that the existing powder-type piezoelectric photocatalyst is easy to agglomerate and difficult to recycle, and realize the actual application of photocatalytic membrane technology in photocatalytic decomposition of water to produce hydrogen. However, the performance of the photocatalytic decomposition of water to produce hydrogen obtained by the invention is not the performance required by this application.
[0008] Chinese patent document CN110075923A discloses a biomimetic construction method and use of a g-C3N4 / BiOI-pDA@PVDF photocatalytic membrane. It uses polydopamine (pDA) to modify PVDF powder, uses freeze casting to prepare a photocatalytic membrane, and is used to remove tetracycline (TC) in a solution. By studying the modified PVDF powder, the problem of photocatalyst and membrane compatibility can be effectively solved, and the catalytic performance of the g-C3N4 / BiO I-pDA@PVDF photocatalytic membrane is further improved. The freeze casting method (i.e., frozen phase conversion method) is used to form an ordered lattice macroporous structure inside the membrane, improve membrane flux, provide more catalytic active sites, and effectively improve catalytic activity. At the same time, the photocatalytic technology is combined with the membrane separation technology to prepare a composite membrane with photocatalytic function, which effectively slows down membrane pollution, is easy to recycle, and is better than a powder catalyst. This invention is also a photocatalytic composite membrane, which improves the degradation rate of the target substance by improving the photocatalytic performance, and is not the performance required by this application.
[0009] Therefore, after searching, no prior art was found that provided a solution to the technical problems faced by polyvinylidene fluoride materials in the process of extracting uranium from seawater. Summary of the invention
[0010] In view of this, the purpose of the present invention is to solve the technical problems existing in the existing seawater uranium extraction adsorption materials, and to provide an anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material and a preparation method thereof, which has an excellent removal rate for uranyl ions and excellent antibacterial properties.
[0011] The technical solutions adopted are:
[0012] The invention discloses an anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material, which uses dimethyl sulfoxide as a solvent, polyvinylidene fluoride as a base material, amidoximized polyacrylonitrile as a modified molecule, and Bi4Ti3O 12 / SnO2 is used as filler, which is made by physical blending and frozen phase transformation method.
[0013] Furthermore, dimethyl sulfoxide is used as a solvent, polyvinylidene fluoride is used as a base material, and Bi4Ti3O 12 / SnO2 as filler to obtain Bi4Ti3O 12 / SnO2 / PVDF casting solution; then, using polyacrylonitrile as the base, polyacrylonitrile is modified with hydroxylamine hydrochloride under alkaline conditions to obtain amidoxime polyacrylonitrile casting solution; finally, the two casting solutions are physically blended to obtain a new casting solution, which is then prepared by a frozen phase inversion method.
[0014] Furthermore, the mass ratio of polyvinylidene fluoride to dimethyl sulfoxide is 2:(12.5-14.5); Bi4T i3O 12 / The mass ratio of SnO2 to polyvinylidene fluoride is 1:(2.2-3.2); the mass ratio of polyacrylonitrile to dimethyl sulfoxide is 2:(10.6-13.6); the mass ratio of polyacrylonitrile to hydroxylamine hydrochloride is 4:(5.1-5.3).
[0015] Furthermore, the mass ratio of polyvinylidene fluoride to dimethyl sulfoxide is 2:13.3; Bi4Ti3O 12 The mass ratio of / SnO2 to polyvinylidene fluoride is 1:2.24; the mass ratio of polyacrylonitrile to dimethyl sulfoxide is 2:13.3; the mass ratio of polyacrylonitrile to hydroxylamine hydrochloride is 4:5.24.
[0016] A method for preparing the anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material of the present invention comprises the following steps:
[0017] S1. Take Bi4T i3O 12 / SnO2 powder was added to dimethyl sulfoxide, and stirred after ultrasonication; polyvinylidene fluoride was added to the mixed solution, and stirred to obtain Bi4Ti3O 12 / SnO2 / PVDF film casting solution;
[0018] S2. Add NH2OH·HCl to dimethyl sulfoxide, stir at room temperature, add NaOH particles after dissolution, and continue stirring; add polyacrylonitrile particles to the solution, heat to the threshold temperature in an oil bath, and after sufficient reaction, centrifuge to remove excess NaOH particles to obtain amidoxime polyacrylonitrile casting solution;
[0019] S3. The two casting liquids obtained from S1 and S2 are mixed and stirred to form a new casting liquid, and then vacuum degassing is performed; the obtained casting liquid is transferred to the surface of a glass plate, placed on the surface of an ice cube for crystallization, and immediately placed in deionized water after complete crystallization to complete phase conversion.
[0020] Furthermore, in step S1, the Bi4Ti3O 12 / SnO2 is prepared by the following steps:
[0021] S11, Ti(OC4H9)4, Bi(NO3)3·5H2O, and sodium oleate were added to a NaOH solution, subjected to a hydrothermal reaction at 180-190°C for 15-16h, and the sample was washed with ethanol and hot distilled water, and then dried at 60-70°C to obtain Bi4T i3O 12 ;
[0022] S12. Prepared Bi4Ti3O 12 Add SnCl4·5H2O and NaOH mixed solution, hydrothermally react at 200-210℃ for 16-17h, wash the sample with ethanol and hot distilled water, and then dry at 60-70℃ to obtain Bi4Ti3O 12 / SnO2.
[0023] Further, in step S12, Bi4Ti3O 12 The mass ratio of Bi4Ti3O to SnCl4·5H2O is 1:3-5; 12 The mass ratio with NaOH is 1:2-3.
[0024] Further, in S3, the amidoximated polyacrylonitrile casting solution obtained in S1 and the Bi4Ti3O 12 The mass ratio of the mixed / SnO2 / PVDF casting solution is 1:4-6.
[0025] Furthermore, in S1, Bi4Ti3O 12 / SnO2 powder was added to dimethyl sulfoxide, ultrasonicated for 30 minutes and then stirred for 30 minutes; polyvinylidene fluoride was added to the mixed solution and stirred at 50℃ for 2 hours to obtain Bi4Ti3O 12 / SnO2 / PVDF film casting solution.
[0026] Further, in S2, NH2OH·HCl was added to dimethyl sulfoxide, stirred at room temperature for 30 minutes, and NaOH particles were added after dissolution, and stirring was continued for 30 minutes; polyacrylonitrile particles were added to the solution, the temperature was raised to 60°C oil bath, and after reacting for 7 hours, the excess NaOH particles were removed by centrifugation to obtain amidoxime polyacrylonitrile casting solution.
[0027] Principles and advantages of the present invention:
[0028] 1. In order to further enhance the adsorption selectivity of polyvinylidene fluoride materials to uranyl ions, the present invention introduces physical blending technology. Physical blending technology refers to using polyvinylidene fluoride as a matrix and amidoxime-functionalized polyacrylonitrile as a functional molecule. The two are connected by hydrogen bonds. The amidoxime-functionalized polyacrylonitrile specifically binds to uranyl ions, thereby improving the selective adsorption-reduction of uranyl ions by polyvinylidene fluoride materials. The present invention uses polyvinylidene fluoride as a base material and amidoxime-functionalized polyacrylonitrile as a functional molecule, and successfully prepares amidoxime-functionalized polyvinylidene fluoride uranium adsorption materials through physical blending technology. The material specifically binds to uranyl ions during the uranium adsorption process, thereby achieving high adsorption selectivity of the material to uranyl ions, and the material preparation operation of this method is simple and convenient.
[0029] 2. In the process of preparing polyvinylidene fluoride composite materials by physical blending technology, the present invention introduces Bi4Ti3O 12 / SnO2 piezoelectric heterojunction as filler, Bi4Ti3O 12 The SnO2 / SnO2 piezoelectric heterojunction is a piezoelectric heterojunction with high-voltage electrocatalytic activity. When subjected to external vibration, it activates its own piezoelectric effect to generate piezoelectric electron-hole pairs, among which the piezoelectric electrons can reduce the adsorbed U(VI) to obtain insoluble U(IV), thereby separating the uranyl ions from the solution; on the other hand, the other piezoelectric electrons and holes undergo reduction and oxidation reactions with oxygen and water to produce a series of active oxygen free radicals, which can combine with bacteria and kill bacteria while reducing U(VI). By introducing Bi4Ti3O 12 / SnO2 piezoelectric heterojunction greatly improves the piezoelectric activity of polyvinylidene fluoride composite materials and also gives polyvinylidene fluoride materials excellent antibacterial properties.
[0030] 3. The present invention introduces frozen phase transformation technology, uses polyvinylidene fluoride as the base material, dimethyl sulfoxide as the solvent, and utilizes the low melting point of dimethyl sulfoxide to transfer the polyvinylidene fluoride based casting liquid to the surface of the glass plate, and places it on the surface of an ice cube for crystallization. After complete crystallization, it is immediately placed in deionized water to complete the phase transformation to obtain a porous polyvinylidene fluoride material.
[0031] Fourth, the present invention introduces physical blending technology, which refers to using polyvinylidene fluoride as a matrix and amidoxime-functionalized polyacrylonitrile as a functional molecule, the two are connected by hydrogen bonds, and amidoxime-functionalized polyacrylonitrile specifically binds to uranyl ions. The amidoxime-functionalized polyvinylidene fluoride film specifically binds to uranyl ions, thereby achieving high adsorption selectivity of the material for uranyl ions. The removal rate of uranyl ions by the amidoxime-functionalized polyvinylidene fluoride film is 1.46 times that of the polyvinylidene fluoride film without amidoxime functionalization.
[0032] 5. The present invention adopts physical blending technology, using polyvinylidene fluoride as the base material, dimethyl sulfoxide as the solvent, amidoximized polyacrylonitrile as the modified molecule, Bi4Ti3O 12 / SnO2 is used as filler and is prepared by frozen phase transformation method. The frozen phase transformation method increases the content of β-phase PVDF and the water flux of the film material. The amidoximated polyacrylonitrile and Bi4Ti3O 12 / SnO2 fillers improved the selectivity and piezoelectric activity, increased the uranyl ion removal rate and endowed the material with antibacterial properties. The amidoxime-functionalized polyvinylidene fluoride film had a uranyl ion removal rate of 99.32% within 4 hours and an antibacterial rate of more than 80% against the three selected bacteria. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the preparation process of Example 1 of the present invention;
[0034] Figure 2 The scanning electron microscope images of the BSPP of Example 1 of the present invention, wherein (a) the front side, (b) the back side, and (c) the cross section;
[0035] Figure 3 The scanning electron microscope images of BSPP-T of comparative example 1 of the present invention, wherein (a) the front side, (b) the back side, and (c) the cross section;
[0036] Figure 4 Bi4Ti3O in Example 1 12 Elemental spectrum (ae) of / SnO2 heterojunction and its Figure 4 f HRTEM micrograph and SAED pattern (inset).
[0037] Figure 5 The XRD patterns of Example 1 and Comparative Example 3 are shown in FIG.
[0038] Figure 6 PFM results of BSPP: (a) surface topology, (b) amplitude, (c) phase images, (d) amplitude-pressure butterfly curve, and (e) piezoelectric response phase hysteresis line.
[0039] Figure 7KPFM results of BSPP: (a) surface morphology, (b) corresponding surface potential image, and (c) surface potential distribution on the selected line of BSPP.
[0040] Figure 8 (a) DRS spectrum, (b) MS image, (c) band gap, (d) band structure images of BTO and SnO2 and Bi4Ti3O 12 Schematic diagram of the energy levels of SnO2.
[0041] Fig. 9 The figure is a comparison of the water flux between Example 1 and Comparative Example 1.
[0042] Fig.10 This is the zeta potential diagram of Example 1.
[0043] Fig.11 The removal rates of uranium in Example 1 and Comparative Example 1 vary with time.
[0044] Fig.12 The uranium removal rate of Example 1 under different pH conditions.
[0045] Fig.13 It is the removal rate of each ion in Example 1 and Comparative Example 2 under the condition of multiple ions.
[0046] Fig.14 This is the cycle performance test of Example 1.
[0047] Fig.15 The results of the pilot test in Example 1 are shown below.
[0048] Fig.16 This is the elemental spectrum of the cross section after the reaction of Example 1.
[0049] Fig.17 The antibacterial effects of Example 1 and Comparative Example 3 are shown. DETAILED DESCRIPTION
[0050] The embodiments of the present invention are described in detail below, but the use and purpose of these exemplary implementations are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to them.
[0051] In the following examples and comparative examples, the abbreviations and chemical names correspond to the following:
[0052] DMSO: dimethyl sulfoxide; PVDF: polyvinylidene fluoride; PAN: polyacrylonitrile; PAO: amidoxime-functionalized polyacrylonitrile; BSPP: porous polyvinylidene fluoride material of Example 1; BSPP-T: conventional phase inversion polyvinylidene fluoride material of Comparative Example 1; BSP: non-amidoxime functionalized material of Example 2.
[0053] Example 1
[0054] The anti-fouling high-voltage electroactive polyvinylidene fluoride uranium adsorption material of this embodiment is prepared by the following steps:
[0055] 1. Preparation of Bi4Ti3O 12 / SnO2 heterojunction, the steps are as follows;
[0056] ①, Ti(OC4H9)4, Bi(NO3)3·5H2O, and sodium oleate were added to NaOH solution, hydrothermally reacted at 180℃ for 15h, and the sample was washed with ethanol and hot distilled water, and then dried at 60℃ to obtain Bi4Ti3O 12 ;
[0057] ② Prepare Bi4Ti3O 12 Add SnCl4·5H2O and NaOH mixed solution, hydrothermally react at 200℃ for 16h, wash the sample with ethanol and hot distilled water, and then dry at 60℃ to obtain Bi4Ti3O 12 / SnO2, of which Bi4Ti3O 12 The mass ratio of Bi4Ti3O to SnCl4·5H2O is 1.2g:4.3g. 12 The mass ratio of to NaOH is 1g:2.4g.
[0058] 2. Preparation of porous polyvinylidene fluoride material (i.e., anti-fouling high-voltage electroactive polyvinylidene fluoride uranium adsorption material), the steps are as follows:
[0059] ①, take Bi4Ti3O 12 / SnO2 powder was added to DMSO, ultrasonicated for 30 min and then stirred for 30 min; PVDF was added to the mixed solution and stirred at 50 °C for 2 h to obtain Bi4Ti3O 12 / SnO2 / PVDF film casting solution;
[0060] ②, add NH2OH·HCl to DMSO, stir at room temperature for 30 minutes, add NaOH particles after dissolution, and continue stirring for 30 minutes; add PAN particles to the solution, heat to 60℃ oil bath, react for 7 hours, centrifuge to remove excess NaOH particles to obtain PAO casting solution;
[0061] ③. The two casting solutions were mixed and stirred to form a mixed casting solution, and then vacuum degassing was performed for 30 min. The obtained casting solution was transferred to the surface of a glass plate, placed on the surface of an ice cube for crystallization, and immediately placed in deionized water after complete crystallization to complete phase transformation to obtain a porous polyvinylidene fluoride material (denoted as BSPP). The mass of the PAO casting solution was similar to that of the Bi4Ti3O 12The mass ratio of / SnO2 / PVDF casting solution is 1g:5g.
[0062] Figure 1 This is a schematic diagram of the preparation process of Example 1.
[0063] This embodiment adopts physical blending technology, using polyvinylidene fluoride as the base material, dimethyl sulfoxide as the solvent, amidoximized polyacrylonitrile as the modified molecule, Bi4Ti3O 12 / SnO2 is used as filler and is made by frozen phase transformation method. The frozen phase transformation method increases the content of β-phase PVDF and improves the water flux of the film material. The amidoximated polyacrylonitrile and Bi4Ti3O 12 / SnO2 fillers improve the selectivity and piezoelectric activity, respectively, enhance the uranyl ion removal rate and endow the material with antibacterial properties.
[0064] Comparative Example 1
[0065] Referring to Example 1, compared with Example 1, this comparative example does not perform frozen phase transformation, but traditional phase transformation. That is, the other steps are the same, except that Example 1 is a phase transformation after freezing, and this comparative example is a direct phase transformation without freezing.
[0066] Specifically, this comparative example is completed according to the following steps:
[0067] 1. Preparation of Bi4Ti3O 12 / SnO2 heterojunction:
[0068] ①, Ti(OC4H9)4, Bi(NO3)3·5H2O, and sodium oleate were added to NaOH solution, hydrothermally reacted at 180℃ for 15h, and the sample was washed with ethanol and hot distilled water, and then dried at 60℃ to obtain Bi4Ti3O 12 ;
[0069] ② Prepare Bi4Ti3O 12 Add SnCl4·5H2O and NaOH mixed solution, hydrothermally react at 200℃ for 16h, wash the sample with ethanol and hot distilled water, and then dry at 60℃ to obtain Bi4Ti3O 12 / SnO2, of which Bi4Ti3O 12 The mass ratio of Bi4Ti3O to SnCl4·5H2O is 1.2g:4.3g. 12 The mass ratio of to NaOH is 1g:2.4g.
[0070] 2. The traditional phase inversion method for preparing polyvinylidene fluoride material includes the following steps:
[0071] ①, take Bi4Ti3O 12 / SnO2 powder was added to DMSO, ultrasonicated for 30 min and then stirred for 30 min; PVDF was added to the mixed solution and stirred at 50 °C for 2 h to obtain Bi4Ti3O 12 / SnO2 / PVDF film casting solution;
[0072] ②, add NH2OH·HCl to DMSO, stir at room temperature for 30 minutes, add NaOH particles after dissolution, and continue stirring for 30 minutes; add PAN particles to the solution, heat to 60℃ oil bath, react for 7 hours, centrifuge to remove excess NaOH particles to obtain PAO casting solution;
[0073] ③. The two casting solutions were mixed and stirred to form a mixed casting solution, and then vacuum degassing was performed for 30 min. The obtained casting solution was transferred to the surface of a glass plate and immediately placed in deionized water to complete phase inversion to obtain a conventional phase inversion polyvinylidene fluoride material (denoted as BSPP-T). The mass of the PAO casting solution was similar to that of the Bi4Ti3O 12 The mass ratio of / SnO2 / PVDF casting solution is 1g:5g.
[0074] Comparative Example 2
[0075] Referring to Example 1, compared with Example 1, the difference between this example and Example 1 is that no PAO casting solution is added in step 2③. The other steps are the same as those in Example 1.
[0076] In this comparative example, no PAO casting solution was added, that is, the polyvinylidene fluoride based material was not functionalized by amidoxime, and the product was BSP. As a result, the polyvinylidene fluoride based material had a poor selective removal rate for uranyl ions.
[0077] Comparative Example 3
[0078] Referring to Example 1, compared with Example 1, the difference between this example and Example 1 is that Bi4Ti3O is not added in step 2①. 12 / SnO2 powder, and no PAO casting solution is added in step 2③. The other steps are the same as those in Example 1.
[0079] In this comparative example, only the PVDF casting solution was subjected to frozen phase transformation. No Bi4Ti3O 12 / SnO2 powder, so its piezoelectric properties are poor and it shows poor performance in the antibacterial experiment.
[0080] Specifically, scanning electron microscopy was performed on the BSPP prepared in Example 1 and the BSPP-T prepared in Comparative Example 1. Figures 2 to 3 As shown, Figure 2 is a scanning electron microscope image of BSPP prepared in Example 1, Figure 3 This is a scanning electron microscope image of the BSPP-T prepared in Comparative Example 1; Figures 2 to 3 It can be seen that BSPP has a porous structure, which proves that the frozen phase transformation method successfully creates pores. The SEM image of BSPP shows that it has a through-hole structure, which is beneficial to the UO2 2+ adsorption.
[0081] Figure 4 Bi4Ti3O in Example 1 12 Elemental maps (ae) and HRTEM micrographs and SAED patterns of the SnO2 / SnO2 heterojunction (inset).
[0082] Figure 5 The XRD patterns of Example 1 and Comparative Example 3 are shown in FIG.
[0083] Figure 6 PFM results of BSPP: (a) surface topology, (b) amplitude, (c) phase images, (d) amplitude-pressure butterfly curve, and (e) piezoelectric response phase hysteresis line.
[0084] Figure 7 KPFM results of BSPP: (a) surface morphology, (b) corresponding surface potential image, and (c) surface potential distribution on the selected line of BSPP.
[0085] Figure 8 (a) DRS spectrum, (b) MS image, (c) band gap, (d) band structure images of BTO and SnO2 and Bi4Ti3O 12 Schematic diagram of the energy levels of SnO2.
[0086] Fig. 9 The water flux of Example 1 and Comparative Example 1 is compared; Figure 5 It can be seen that the BSPP water flux is 795.85 L m -2 ·h -1 , while the water flux of BSPP-T was 305.63 L m -2 ·h -1 .
[0087] Fig.10 is the zeta potential diagram of Example 1; Figure 6 It can be seen that the Zeta potential of BSPP at different pH values has a zero potential point at pH = 4.84.
[0088] Fig.11 The removal rate of uranium in Example 1 and Comparative Example 1 varies with time; Fig.11 It can be seen that BSPP has a significant effect on UO2 at 240 min. 2+ The removal rate reached 99.32%, while that of BSPP-T was 74.58%.
[0089] Fig.12 is the uranium removal rate of Example 1 under different pH conditions; Figure 7 It can be seen that the optimal pH for uranium removal by BSPP is 7.
[0090] Fig.13 is the removal rate of each ion in Example 1 and Comparative Example 2 under the condition of multiple ions; Fig.13 It can be seen that in the presence of various ions (U, Zn, Cu, Ni, Co, Fe, V and Pb), the adsorption selectivity of BSPP and BSP adsorbents for uranium was studied. Compared with the non-amidoxime functionalized material BSP, the selective adsorption effect of BSPP on uranium is more obvious. The removal rate of uranium by the amidoxime functionalized material BSPP is as high as 85.39%, while the removal rate of uranium by BSP is only 58.36%.
[0091] Fig.14 The cycle performance test of Example 1 is as follows; Fig.14 It can be seen that BSPP has excellent recycling performance. After five cycles, the removal rate of uranyl ions by BSPP only dropped to 95%.
[0092] Fig.15 This is the pilot test result of Example 1. Fig.15 It can be seen that the inventor designed a device that slowly pumps the uranium-containing liquid into the pipeline through a water pump. The water flows from top to bottom to pre-wash the film in the pipeline, and the water flow stimulates its own piezoelectric effect, thereby realizing the extraction of uranium. Pour the prepared 15L spiked simulated seawater into the container in advance, put the BSPP into the pipeline at the same time, and then start the water pump to start the experiment. Sample 5mL at the specified time point to determine the concentration of uranium (VI). As shown in the figure, within 30 days, the uranium enrichment dropped from 839μg / L to 351μg / L, and the adsorption capacity was 2440mg / m 2 This result suggests that BSPP membranes have the potential to extract uranium by utilizing mechanical energy from nature.
[0093] Fig.16 This is the elemental spectrum of the cross section after the reaction of Example 1. Fig.16 It can be seen that after the reaction, BSPP maintains its original morphology, reflecting its stability; and the cross section is filled with uranium elements, proving the importance of pores in the reaction process.
[0094] Fig.17 In order to test the antibacterial effect of Example 1 and Comparative Example 3, three bacteria, namely Gram-positive Staphylococcus aureus, Gram-negative Escherichia coli and Pseudoalteromonas, were selected for antibacterial performance testing. Fig.17It can be seen that in the blank control group, the total number of bacteria remained basically unchanged under ultrasound and non-ultrasound conditions, proving that ultrasound itself does not affect bacterial growth. Compared with the blank control, the number of bacteria on the surface of the culture dish of PVDF has decreased to a certain extent, proving that pure PVDF also has a certain antibacterial ability under ultrasound conditions. Compared with the blank control, the number of bacteria on the surface of the culture dish of BSPP has greatly decreased, proving that BSPP has a strong antibacterial ability under ultrasound conditions. This is because under ultrasound conditions, BSPP activates its own piezoelectric effect, and the generated active oxygen free radicals attack and kill bacteria, thereby achieving an antibacterial effect.
[0095] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A fouling-resistant high-voltage electrocatalytically active polyvinylidene fluoride uranium adsorption material, characterized in that: Using dimethyl sulfoxide as solvent, polyvinylidene fluoride as base material, amidoximized polyacrylonitrile as modified molecule, Bi4Ti3O 12 / SnO2 is used as filler, which is made by physical blending and frozen phase transformation method.
2. The anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to claim 1, characterized in that: First, dimethyl sulfoxide was used as solvent and polyvinylidene fluoride was used as substrate material. 12 / SnO2 as filler to obtain Bi4Ti3O 12 / SnO2 / PVDF casting solution; then, using polyacrylonitrile as the base, polyacrylonitrile is modified with hydroxylamine hydrochloride under alkaline conditions to obtain amidoxime polyacrylonitrile casting solution; finally, the two casting solutions are physically blended to obtain a new casting solution, which is then prepared by a frozen phase inversion method.
3. The anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to claim 2, characterized in that: The mass ratio of polyvinylidene fluoride to dimethyl sulfoxide is 2:(12.5-14.5); Bi4Ti3O 12 / The mass ratio of SnO2 to polyvinylidene fluoride is 1:(2.2-3.2); the mass ratio of polyacrylonitrile to dimethyl sulfoxide is 2:(10.6-13.6); the mass ratio of polyacrylonitrile to hydroxylamine hydrochloride is 4:(5.1-5.3).
4. The anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to claim 3, characterized in that: The mass ratio of polyvinylidene fluoride to dimethyl sulfoxide is 2:13.3; Bi4Ti3O 12 The mass ratio of / SnO2 to polyvinylidene fluoride is 1:2.24; the mass ratio of polyacrylonitrile to dimethyl sulfoxide is 2:13.3; the mass ratio of polyacrylonitrile to hydroxylamine hydrochloride is 4:5.
24.
5. A method for preparing the anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to any one of claims 1 to 4, characterized in that: The steps include: S1. Take Bi4Ti3O 12 / SnO2 powder was added to dimethyl sulfoxide, and stirred after ultrasonication; polyvinylidene fluoride was added to the mixed solution, and stirred to obtain Bi4Ti3O 12 / SnO2 / PVDF film casting solution; S2. Add NH2OH·HCl to dimethyl sulfoxide, stir at room temperature, add NaOH particles after dissolution, and continue stirring; add polyacrylonitrile particles to the solution, heat to the threshold temperature in an oil bath, and after sufficient reaction, centrifuge to remove excess NaOH particles to obtain amidoxime polyacrylonitrile casting solution; S3. The two casting liquids obtained from S1 and S2 are mixed and stirred to form a new casting liquid, and then vacuum degassing is performed; the obtained casting liquid is transferred to the surface of a glass plate, placed on the surface of an ice cube for crystallization, and immediately placed in deionized water after complete crystallization to complete phase conversion.
6. The method for preparing the anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to claim 5, characterized in that: In step S1, the Bi4Ti3O 12 / SnO2 is prepared by the following steps: S11. Add Ti(OC4H9)4, Bi(NO3)3·5H2O and sodium oleate to NaOH solution, perform hydrothermal reaction at 180-190℃ for 15-16h, wash the sample with ethanol and hot distilled water, and then dry at 60-70℃ to obtain Bi4Ti3O 12 ; S12. Prepared Bi4Ti3O 12 Add SnCl4·5H2O and NaOH mixed solution, hydrothermally react at 200-210℃ for 16-17h, wash the sample with ethanol and hot distilled water, and then dry at 60-70℃ to obtain Bi4Ti3O 12 / SnO2.
7. The method for preparing the anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to claim 6, characterized in that: In step S12, Bi4Ti3O 12 The mass ratio of Bi4Ti3O to SnCl4·5H2O is 1:3-5; 12 The mass ratio with NaOH is 1:2-3.
8. The method for preparing the anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to claim 5, characterized in that: In S3, the amidoximated polyacrylonitrile casting solution obtained in S1 and the Bi4Ti3O 12 The mass ratio of the mixed / SnO2 / PVDF casting solution is 1:4-6.
9. The method for preparing the anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to claim 5, characterized in that: In S1, take Bi4Ti3O 12 / SnO2 powder was added to dimethyl sulfoxide, ultrasonicated for 30 minutes and then stirred for 30 minutes; polyvinylidene fluoride was added to the mixed solution and stirred at 50℃ for 2 hours to obtain Bi4Ti3O 12 / SnO2 / PVDF film casting solution.
10. The method for preparing the anti-fouling high-voltage electrocatalytic active polyvinylidene fluoride uranium adsorption material according to claim 5, characterized in that: In S2, NH2OH·HCl was added to dimethyl sulfoxide, stirred at room temperature for 30 minutes, and NaOH particles were added after dissolution, and stirring was continued for 30 minutes; polyacrylonitrile particles were added to the solution, and the temperature was raised to 60°C in an oil bath. After reacting for 7 hours, the excess NaOH particles were removed by centrifugation to obtain amidoxime polyacrylonitrile casting solution.
Citation Information
Patent Citations
Biomimetic construction method of g-C3N4 / BiOI-pDA@PVDF photocatalytic membrane and application thereof
CN110075923A
CN / LiNbO3 / PVDF piezoelectric photocatalysis composite membrane as well as preparation method and application thereof
CN112371175A
Cited By
Cerium oxide / piezoelectric material composite nano-enzyme for antifouling coating as well as preparation method and application of cerium oxide / piezoelectric material composite nano-enzyme
CN121797381A
Mechanical energy driven integrated uranium extraction system and method based on piezoelectric porous medium
CN122010240A
A method for extracting uranium based on fluid kinetic energy-electrochemical energy conversion, filter membrane and system
CN122957914A